Teaching vibrato in the middle school classroom - Humbert, Ashton (Kansas State University, 2024)
The purpose of my project is to teach vibrato to a middle school orchestra class. I chose teaching vibrato as my project because I did not have a full in-depth unit to teach vibrato to my middle school students. Vibrato is an important concept that can be developed before students go to high school, but it is one that is often overlooked in middle school. Teaching vibrato in this manner also gives the students experience with shifting and playing out of first position, which is another needed skill for advancing musicians. Another reason for vibrato is that not many of my students are able to take private lessons. A lot of the study of vibrato is done within private lessons, so I wanted to provide the opportunity for students to learn vibrato in the classroom without having to take lessons. When first developing a plan for the process, I started with the end goal in mind: to have my students implement vibrato in their playing by the time they leave middle school. I wanted there to be a cohesive method to teach basic exercises and developing vibrato for all students on all instruments in my classroom at the same time. The beginning of the process started with the violin and viola players completing exercises that were specific to their instrument while the cello and bass players did exercises that were exclusive to theirs. Once these exercises were implemented, students were performing the exercises for their instrument at the same time. The students then developed the vibrato motion for the second finger and the third finger in third position. This process continued with the first and fourth fingers, and finally playing four note patterns with adding vibrato. Students then moved to first position and performed the same four note patterns to fully develop the vibrato motion and technique. Finally, we added vibrato to a scale that matches our concert repertoire and into our concert repertoire. This process helped my students to advance as musicians and they have another year of middle school to fully develop and become proficient at vibrato before going on to high school. My development as a teacher has come from the coursework I have done during my time at K-State. Through the upper strings and lower strings methods classes, I learned different techniques of teaching vibrato and I was able to improve my own vibrato skills on each instrument. This has helped me to better understand how to develop lessons that will be efficient and effective for my students. Another strong aspect of my learning at K-State is the work done on my teaching philosophy. As I was reading different music education philosophies and developing my own, I learned more about how my personal philosophy plays a part in how I teach and what type of teacher I am. Finalizing my teaching principals has also played a part in developing my project because I believe that middle school is the best time to learn advanced techniques such as vibrato. My education at K-State has also helped to mold my teaching and develop my confidence as an educator. The feedback that I received from my professors and classmates has encouraged me to think outside of the box with lesson planning, teaching methodologies, and conducting.
Keywords: Vibrato; Middle school